"Natural family planning": effective birth control supported by the Catholic Church. Issue 6906 (18th September 1993) - Ryder, R E
Abstract : During 20-22 September Manchester is to host the 1993 follow up to last year's "earth summit" in Rio de Janeiro. At that summit the threat posed by world overpopulation received considerable attention. Catholicism was perceived as opposed to birth control and therefore as a particular threat. This was based on the notion that the only method of birth control approved by the church--natural family planning--is unreliable, unacceptable, and ineffective. In the 20 years since E L Billings and colleagues first described the cervical mucus symptoms associated with ovulation natural family planning has incorporated these symptoms and advanced considerably. Ultrasonography shows that the symptoms identify ovulation precisely. According to the World Health Organisation, 93% of women everywhere can identify the symptoms, which distinguish adequately between the fertile and infertile phases of the menstrual cycle. Most pregnancies during trials of natural family planning occur after intercourse at times recognised by couples as fertile. Thus pregnancy rates have depended on the motivation of couples. Increasingly studies show that rates equivalent to those with other contraceptive methods are readily achieved in the developed and developing worlds. Indeed, a study of 19, 843 poor women in India had a pregnancy rate approaching zero. Natural family planning is cheap, effective, without side effects, and may be particularly acceptable to the efficacious among people in areas of poverty.